CLINICAL COMMUNICATION SKILLS IN THE PROFESSIONAL ACTIVITY OF A DOCTOR - V. M. Zhdan; L.M. Shylkina; O.M. Bieliaieva (Проблеми екології та медицини)
The article considers some aspects of clinical communication between a doctor and a patient. The doctor’s profession inherently faces an indispensable requirement to possess a high level of communicative competence, because whatever the development of medical science and technology, the real help to patients is provided by a doctor. In this regard, various aspects of communication between doctors and patients are constantly in the focus of interest in natural and humanitarian spheres of research, as evidenced by numerous scientific studies of domestic and foreign scientists. The research is interdisciplinary and covers a range of issues related to medical psychology and medical pedagogy, medical ethics and deontology, sociology and sociolinguistics. The authors emphasize that in a patient-centered approach, the skills of clinical communication belong to basic clinical abilities, which minimize factors that can negatively affect the doctor’s success, promoting patient satisfaction with medical care and improving their psycho-emotional state, patient compliance, increasing the effectiveness of diagnosis, treatment, disease prevention, and palliative care. It is observed that the skills of clinical communication are complex and are manifested by the ability to choose appropriate tactics of communication with patients and their relatives, to create a trusting atmosphere and a comfortable psychological environment for the patient; possession of nonverbal and paraverbal components of communication; the ability to conduct educational work with the patient to maintain a healthy lifestyle and give up bad habits; the ability to maintain and encourage patient’s autonomy, prove information about possible complications; persuade the patient to comply; the ability to avoid conflicts or act adequately in a conflict situation with patients. The conclusions state that the skills of clinical communication should be formed from the first steps at a medical university, consolidating them during the entire period of study at the undergraduate and postgraduate stages, as well as refining them in the future through non-formal and informal education.